2006
DOI: 10.1128/cmr.00054-05
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis ofHelicobacter pyloriInfection

Abstract: SUMMARY Helicobacter pylori is the first formally recognized bacterial carcinogen and is one of the most successful human pathogens, as over half of the world's population is colonized with this gram-negative bacterium. Unless treated, colonization usually persists lifelong. H. pylori infection represents a key factor in the etiology of various gastrointestinal diseases, ranging from chronic active gastritis without clinical symptoms to peptic ulceration, gastric adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
1,952
0
96

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 2,039 publications
(2,078 citation statements)
references
References 703 publications
(741 reference statements)
30
1,952
0
96
Order By: Relevance
“…Various studies have reported that sex is not associated with increased risk of H. pylori infection 33, 34, 35. In industrialized countries, the prevalence of H. pylori infection is low in childhood and slowly increases with age 2. Several groups have reported increasing H. pylori seroprevalence according to age, and it is hypothesized that this increase is attributable to a birth cohort phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported that sex is not associated with increased risk of H. pylori infection 33, 34, 35. In industrialized countries, the prevalence of H. pylori infection is low in childhood and slowly increases with age 2. Several groups have reported increasing H. pylori seroprevalence according to age, and it is hypothesized that this increase is attributable to a birth cohort phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were based on the questionnaire developed by the ARIBBA (Alliance for Research in El Barrio, New York, and Bayamón) Project, a study that evaluated factors that influenced risk behaviors among Puerto Rican injection drug users 19. Two field managers visited every selected occupied household, where subjects that agreed to participate in the study completed the following procedures:1 informed consent and pretest counseling;2 a personal interview to obtain information about sociodemographic characteristics, medical history, tattooing and body piercing practices, knowledge on viral infections, and self‐report of hepatitis A and hepatitis B vaccination;3 an audio computer‐assisted self‐interview to ascertain cigarette and alcohol use, drug use, sex‐related risk behaviors, and history of incarceration; and4 collection of blood and urine samples. Of the selected residents, 1654 (77.9%) participated in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect the strain that we used, the route of exposure, or may simply mean that we did not account for some crucial piece of the puzzle that is yet unknown about the transmission of H. pylori via water. The genetic variability of H. pylori strains is vast,33 so it may be possible that some strains lack the capability to persist in water, but instead are transmitted only via other exposures, such as person‐to‐person or fecal‐oral routes 4…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori infection is hypothesized to be transmitted through multiple routes, including vertically from mother to child and through contaminated reservoirs like food and water 3, 4. A body of evidence suggests that contaminated water may be a source of H. pylori infection, with epidemiological studies consistently associating H. pylori infection with lack of access to potable drinking water and proper sanitation 3, 5, 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%